Kapok derived activated carbon catalyst assisted in biodiesel production from waste cooking oil / Jeyashelly Andas and Nur Adilah Zahari - Andas, Jeyashelly; Zahari, Nur Adilah (Research Management Institute (RMI), 2024)
The present study aims to synthesize green carbon-based catalyst from kapok (Ceiba pentandra) using two different activating agents: KOH (CB1) and K2CO3 (CB2) with 1:1.0 (raw material: activating agent), at activation temperature of 400 °C and impregnation time of only 15 min. The synthesized catalysts were evaluated in the transesterification of waste cooking oil (WCO) into biodiesel. CB1 registered higher iodine number and percentage yield (1446.30 mg/g, 62.60 %) compared to 1200.23 mg/g and 53.50 % obtained for CB2. Several physico-chemical characterizations were subjected for kapok and the carbon catalysts such as Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM) and CHNS/O Analyzer. FTIR investigation showed the disappearance or reduction in peak intensity of several peaks at 1512-1200 cm-1 in the carbon catalyst compared to raw kapok, arising due to carbonization and activation processes. CHNSO analysis verified that both CB1 and CB2 registered high carbon content of 63.93 % and 62.86 %, respectively compared to the raw kapok (43.54 %). Morphological studies by SEM analysis showed appearance of cylindrical tube for all the samples. The biodiesel synthesis from WCO at 0.2 wt.% catalyst loading, methanol to oil (molar ratio of 3:1), reaction temperature of 60 ˚C for 1 h resulted in high catalysis over CB1 (89.57 %), followed by CB2 (87.46 %) and without catalyst (35.46 %). Large iodine number and high carbon content exhibited by CB1 was the probable reasoning for the accelerated activity of CB1 in the transesterification of WCO. To conclude, the present work showed a successful conversion of waste biomass into promising carbon catalyst for green synthesis of biodiesel from WCO.